Enterocutaneous fistula et cause abdominal tuberculosis in community: An emergency diagnosis challenge - Hadi, Siusanto; Ferdinandus, Pieter David Adriaan; Wartiningsih, Minarni; Messakh, Billy Daniel; Agung, Purwakaning Purnomo; Sekarputri , Cempaka Harsa; Gonaldy, Vincent Aurelius (Malahayati International Journal of Nursing and Health Science, 2025)
Background: A fistula is defined as an abnormal connection that connects two hollow spaces of the body. Fistula are divided into two categories, internal and external. Abdominal TB can mimicks other diseases including Enterocutaneous fistula that occur due to chron’s disease, malignancy, typhoid or radiation exposure. Tuberculosis is a rare cause of enterocutaneous fistula increasing the needs of clinicians to diagnose TB in an emergency manner. Purpose: To assess clinical manifestation of enterocutaneous fistula in patient with abdominal tuberculosis, and to determine the best emergency diagnosis tools in the progress of diagnosing abdominal tuberculosis. Method: This literature review is guided by the PICOS framework, encompassing materials published from 2000 to 2024. Data were obtained from diverse sources such as PubMed Central, Google Scholar, Science Direct, Elsevier (SCOPUS), scientific journals, articles, and books. The analysis proceeded through three stages: data reduction, presentation, and formulation of conclusions. Studies fulfilling the inclusions criteria were selected. Results: Patient with TB could have enterocutaenous fistula as one of its clinical manifestations, therefore. This study concludes that multiplex PCR shows an outstanding result for its specificity making it highly effective in ruling out non-tubercular diseases with minimum false positive. Conclusion: Enterocutaneous fistula in intestinal tuberculosis often presents without clear thoracic imaging of pulmonary TB, complicating diagnosis. Abdominal TB's non-specific symptoms can mimic other diseases, making CT scans and ultrasonography useful, though not definitive. Laparoscopy, combined with histological examination, remains the most reliable diagnostic tool. Laboratory tests like ADA levels, PCR, and culture are essential in confirming the diagnosis. A diagnostic algorithm and early anti-tubercular therapy can help when test results are inconclusive.